Detection of the Genetic Material of the Viruses Tacheng uukuvirus and Sara tick phlebovirus in Taiga Ticks Collected in the Sverdlovsk, Tomsk Regions and Primorsky Territory of Russia and Their Phylogeny - N. L. Tupota; V. A. Ternovoi; E. P. Ponomareva; R. B. Bayandin; A. N. Shvalov; B. S. Malyshev; T. V. Tregubchak; T. V. Bauer; E. V. Protopopova; N. K. Petrova; E. V. Zhebrovskaya; E. G. Burukhina; et al. (Проблемы особо опасных инфекций, 2023)
Extensive spread of tick-borne diseases poses a significant problem for public health and the health of the population living in endemic areas.The aim of the study was to search, analyze genetic material and identify new viral agents of the Phenuiviridae family in taiga ticks collected in Asian regions of Russia using the method of high throughput sequencing.Materials and methods. The study involved 1460 taiga ticks collected in suburban areas of the Tomsk, Yekaterinburg and Primorsky Territory. The genetic material isolated from ticks was sequenced using Illumina technology followed by phylogenetic analysis.Results and discussion. Analysis of the sequencing results made it possible to detect extended nucleotide sequences of the L-gene fragment characteristic of the Phenuiviridae family viruses. We were able to identify 20 nucleotide sequences the length of 250 bp on average in homogenates of Ixodes persulcatus ticks. Eighteen isolates have been identified as members of the genus Uukuvirus and two isolates have been assigned to the genus Phlebovirus, Phenuiviridae family. Phylogenetic analysis has shown that all isolates of the genus Uukuvirus fall under the cluster of Tacheng tick virus 2 belonging to the species Tacheng uukuvirus. They form a separate phylogenetic group which is closely related to two Romanian variants of 2019. Tacheng tick virus 2 was detected in all three surveyed regions of the Asian part of Russia. Two Tomsk isolates of phlebovirus were classified as Sara tick phlebovirus and they clustered with two isolates of phleboviruses from Karelia. Thus, the genetic material of Tacheng tick virus 2 and Sara tick phlebovirus belonging to two genera of the family Phenuiviridae was found in I. persulcatus ticks collected in three geographically different regions of the Asian part of Russia.